(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the voice development of preschool children, focusing on its physiological, psychological, and pedagogical aspects. The human voice is the first musical instrument a child encounters, and its development during early childhood has a profound impact on communication, emotional expression, and musical ability. Preschool age is a critical period for cultivating healthy vocal habits, as the vocal apparatus is still fragile and developing. The article highlights the main stages of vocal growth, the challenges educators face in guiding children’s voices, and the role of play, creativity, and supportive environments in nurturing proper vocal development.